Doping analysis for steroid and differentiation of their origins (Review) - UEKI, Makoto (Bunseki kagaku, 2001)
Doping control is conducted at national and international sports events using cutting-edge analytical techniques. Most problematic doping agents used by athletes to enhance performance are a series of anabolic androgenic steroids, so called 'muscle-enhancing drugs'. Some 37.1% out of 2,624 positive doping cases in 1999 proved to be due to the use of anabolic steroids according to laboratory statistics reported by the medical commission of the International Olympic Committee. Although the majority of the detected doping agents are synthetic anabolic steroids which do not exist in nature, doping cases with naturally occurring anabolic androgenic steroids are also increasing. Because most anabolic steroids are extensively metabolized in the human body and excreted into the urine very rapidly, the parent drug is not detectable within a few days after administration. Thus, the detectability of doping depends on selecting of the analyte, the target compound to be monitored, and the sensitivity method used. For naturally occurring hormones, positive test results have to be supported by additional scientific evidence that shows the heterogeneity of the origin of the target compounds. One example of such strategies is an indirect statistical evaluation by comparing the analysis results with those obtained from non-doping subjects. We developed a carbon isotope methodology for differentiation between exogenous and endogenous compounds, which was applied for the first time in Olympic history in 1998 to detect doping with naturally occurring testosterone-related steroids. The source of human physiological steroids is a mixture of food cholesterol from meat, fish, poultry etc., but commercially available steroids are usually synthesized from phytosterols which exist in C3-plants having a lower 13C-content than animal sterols. The present status of comprehensive screening of steroids, and the latest strategy to enhance both the sensitivity and specificity of the testing system, are discussed in this report.